A PROSPECTIVE STUDY ON ROLE OF VITAMIN E SUPPLEMENTATION IN TYPE 2 DIABETES MELLITUS - D, Pavithra; D, Praveen; M, Vijey Aanandhi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Aim and Objective: The aim of the study was to evaluate the role of Vitamin E supplementation in Type II diabetes mellitus (DM), to determines whether people with Type II DM treated with hypoglycemic agents alone, with or without Vitamin E, to determines the drug interaction in such treatment regimen, and to evaluates the Safety of the regimen. Methods: Type II DM patients with or without complications were included in this study along with serum glycated hemoglobin (HbA1c) concentration between 7.5% and 9.5%. They are divided into test group (which received hypoglycemic agent along with Vitamin E 4000 IU) and control group. Body mass index (BMI) status, fasting blood sugar (FBS), and post-prandial blood sugar (PPBS) were noted once in a month, HbA1c percentage, total cholesterol level (TC), and serum Vitamin E level were estimated and noted for every 3 months at total 9 months of this study. Patients with other comorbid conditions were prominent in this study. Results: It is perceptible with the analysis of obtained data that FBS, PPBS, HbA1c percentage, TC level, and BMI status of the patients were declined gradually in test group (patients with Vitamin E supplementation along with their hypoglycemic agents). Thus, antioxidant therapy is highly propitious whereby delaying the onset of complications in patients with DM. This development would be highly helpful for diabetic patients.